Media and celebrity: Towards a postmodern understanding of the role of reality television in the development of new forms of South African/African celebrity. - De Sibandze, Elva Gómez; Garside, Damian (My University, 2009)
In our paper we deal with the issue of media celebrity in a South African context, focusing on the role reality television has played in regard to emergent forms of new South African celebrity, and determining the social and cultural meaning of these emergent forms in an African socio-political and cultural context. The paper discusses the way in which such celebrities and local audiences’ fascination with them are constructed. We further analyze indigenous and “imported” reality television forms and formats in our investigation in order to explore the phenomenon from the perspective of such antithetical binaries as stardom and celebrity, private identity and public personality, dramatic art/and dramatized reality, and entertainment/ exploitation. We raise issues that are central to understanding the way in which the media functions in postmodern South Africa, assessing the way in which reality TV and reality TV celebrities reflect either an “empowering” freeing up of cultural spaces, or, alternatively, a closing down of such cultural spaces as an expression of late capitalist/postmodern “comodification” and of increasingly invasive forms of technological surveillance – famously expressed by Michel Foucault with his notion of the “panopticon.” This critique, expressed in its strongest form, views reality television as destroying essential ontological distinctions between reality and media image in constructing a virtual realm of the celebrity “real” (here Baudrillard’s notions of the “spectacle” and the “simulacrum” are most apposite). In regard to what is, for post-apartheid South Africa, the crucial issue of identity, we consider the degree to which reality television exploits postmodern anxieties such as the fear of loss of value, status and identity as part of wider transnational and globalizing processes of social, cultural and psychological dislocation.
Keywords: Media and celebrity - Africa; Celebrity and celebrities - Africa; Reality television - Africa; South African celebrities; African celebrities